(Invited) Development of New High-Dielectric Constant Thin Films By Combinatorial Synthesis. (24th April 2020) - Nagata, Takahiro
Abstract : The development of high-dielectric constant film materials is essential for future active and passive nanoelectronics devices. By using combinatorial synthesis, high throughput material development, we developed high-dielectric constant film materials for film capacitor and gate dielectrics. In this paper, the combinatorial synthesis method and achievements concerning the dielectric materials for high temperature operational thin film capacitor and high-k dielectrics are briefly introduced.